Inovasi Pelayanan Publik Di Kantor Dinas Dukcapil Kabupaten Bojonegoro - Wicaya Ningrum; Siti Nur Faizah; Tio Georgia Rangga; Sinta Adia Pramesti (Jurnal Relasi Publik, 2024)
Department of Population and Civil Registration is a government agency engaged in the field of public services. Public services conducted include related to the management of identity cards (KTP), Family Cards (KK), birth certificates and letters or death certificates. As the implementation of Law No. 25 of 2009 article 7 Paragraph (4) letter c, on public services, it is applied in 2014 as the year of public service innovation as an effort to focus on policy and implementation of targeted, in-depth and sustainable policies in building public service innovation within ministries/ institutions/ local governments which is expected to encourage the acceleration of bureaucratic reform. This research method uses a descriptive type of research with a qualitative approach which is to describe how innovations developed from the development of public services in the Department of Population and Civil Registry Bojonegoro. Applied innovations include digitalization of administrative processes, the use of Integrated Information Systems and Human Resource Capacity Building. This digitalization allows people to access services more easily and quickly through online platforms, reducing waiting times and eliminating bureaucratic barriers that previously hindered efficiency.